The effect of nicotinamide adenine dinucleotide phosphate oxidase 4 on migration and invasion of fibroblast-like synoviocytes in rheumatoid arthritis - Ha-Reum Lee; Su-Jin Yoo; Jinhyun Kim; In Seol Yoo; Chan Keol Park; Seong Wook Kang (Arthritis Research & Therapy, 2020)
Abstract Background Reactive oxygen species (ROS) regulate the migration and invasion of fibroblast-like synoviocytes (FLS), which are key effector cells in rheumatoid arthritis (RA) pathogenesis. Nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) induces ROS generation and, consequently, enhances cell migration. Despite the important interrelationship between RA, FLS, and ROS, the effect of NOX4 on RA pathogenesis remains unclear. Methods FLS isolated from RA (n = 5) and osteoarthritis (OA, n = 5) patients were stimulated with recombinant interleukin 17 (IL-17; 10 ng/ml) and tumor necrosis factor alpha (TNF-α; 10 ng/ml) for 1 h. Cell migration, invasion, adhesion molecule expression, vascular endothelial growth factor (VEGF) secretion, and ROS expression were examined. The mRNA and protein levels of NOX4 were analyzed by RT-qPCR and western blotting, respectively. The NOX4 inhibitor GLX351322 and NOX4 siRNA were used to inhibit NOX4 to probe the effect of NOX4 on these cellular processes. Results Migration of RA FLS was increased 2.48-fold after stimulation with IL-17 and TNF-α, while no difference was observed for OA FLS. ROS expression increased in parallel with invasiveness of FLS following cytokine stimulation. When the expression of NOX was examined, NOX4 was significantly increased by 9.73-fold in RA FLS compared to unstimulated FLS. Following NOX4 inhibition, cytokine-induced vascular cell adhesion molecule 1 (VCAM1), VEGF, and migration and invasion capacity of RA FLS were markedly decreased to unstimulated levels. Conclusion NOX4 is a key contributor to cytokine-enhanced migration and invasion via modulation of ROS, VCAM1, and VEGF in RA FLS.